The Efficacy of Augmented Reality on Student Achievement and Perception among Teluk Intan Community College Student in Learning 3D Animation - Siti Nur Shuhada Abu Samah (International Journal of Multimedia and Recent Innovation, 2020)
This paper presents a research conducted in Teluk Intan Community College aimed to evaluate the effectiveness and usability of integrating the Augmented Reality (AR) technology as an aid for animation course in Teluk Intan Community College. The focus was to integrate AR tool as an aid for students in the task of 3D modelling. For this research, the intended outcome is to compare the effectiveness between using the AR tool and written tutorial. The AR tool which later be called as ARC-3DM (Augmented Reality Courseware for 3D Modelling) will be developed and be tested in the experiment. Quantitative approach and quasi-experimental design were used in the study. A total of 54 animation students are involved in the study. The students were divided into two groups: control and treatment. A pretest and posttest were conducted to both groups. System Usability Scale (SUS) Questionnaire were administered to treatment group after the posttest to evaluate usability. Statistical methods involved were descriptive analysis and the analysis of covariance (ANCOVA) with the pretest as the covariate at significant level of 0.05 was conducted to answer the hypothesis. The results indicate that the treatment group performed better than the control group in completing the task of 3D modelling. In terms of usability, the results showed that most of the students agreed on the usability in the ARC-3DM.